Molecular phylogeography and genetic diversity of Angiostrongylus cantonensis and A. malaysiensis (Nematoda: Angiostrongylidae) based on 66-kDa protein gene - Eamsobhana, Praphathip; Yong, Hoi Sen; Song, Sze Looi; Gan, Xiao Xian; Prasartvit, Anchana; Tungtrongchitr, Anchalee (Elsevier, 2019)
Angiostrongylus cantonensis is the main causative agent of human angiostrongyliasis. A sibling species, A. malaysiensis has not been unequivocally incriminated to be involved in human infections. To date, there is only a single report on the application of the partial 66-kDa protein gene sequence for molecular differentiation and phylogeny of Angiostrongylus species. Nucleotide sequences of the 66-kDa protein gene of A. cantonensis and A. malaysiensis from Thailand, as well as those of the laboratory strains of A. cantonensis from Thailand and Hawaii, A. cantonensis from Japan and China, A. malaysiensis from Malaysia, and A. costaricensis from Costa Rica, were used for the reconstruction of phylogenetic tree by the maximum likelihood (ML) method and the haplotypes by the median joining (MJ) network. The ML phylogenetic tree contained two major clades with a full support bootstrap value – (1) A. cantonensis and A. malaysiensis, and (2) A. costaricensis. A. costaricensis was basal to A. cantonensis and A. malaysiensis. The genetic distance between A. cantonensis and A. malaysiensis ranged from p =.82% to p = 3.27%, that between A. cantonensis and A. costaricensis from p = 4.90% to p = 5.31%, and that between A. malaysiensis and A. costaricensis was p = 4.49% to p = 5.71%. Both A. cantonensis and A. malaysiensis possess high 66-kDa haplotype diversity. There was no clear separation of the conspecific taxa of A. cantonensis and A. malaysiensis from different geographical regions. A more intensive and extensive sampling with larger sample size may reveal greater haplotype diversity and a better resolved phylogeographical structure of A. cantonensis and A. malaysiensis.